PERCENTAGE OF LIVER, HEART, BILE, AND SPLEEN OF 35 DAYS AGE BROILER THAT WERE GAVE DRAGON FRUIT SKIN JUICE THROUGH DRINKING WATER - I W. P., Widnyana; Umiarti, A. T.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the effect of giving dragon fruit peel juice in drinking water to the percentage of digestive aids in broilers aged 35 days. The research design used was a completely randomized design (CRD) consisting of 4 treatments and 4 replications, each replication containing 4 broilers. The treatments used were, P0: broilers given drinking water without a mixture of dragon fruit peel juice (control), P1: broilers given drinking water with 2% dragon fruit peel juice mixture, P2: broilers given drinking water with 4% juice mixture. dragon fruit peel, P3: broiler given drinking water with 6% mixture of dragon fruit peel juice. The variables observed were the percentage of the liver, the percentage of the heart, the percentage of bile, and the percentage of the spleen. The results showed that broilers who were given dragon fruit peel juice 2%, 4%, 6% into drinking water had a percentage of liver, heart and spleen that were not significantly different (P>0.05) while broiler bile had a significant effect (P<0 0.05) compared to the control. Based on the results of this study, it can be concluded that the use of 2%, 4% and 6% dragon fruit peel juice into drinking water did not affect the percentage of liver, heart, and spleen however, 4% and 6% treatment decreased the percentage of bile in broilers aged 35 days. Keywords: dragon fruit skin, digestive aid organs